Nowe zadania w zarządzaniu zasobami ludzkimi - Penc, Józef (Wydawnictwo Media Press, 2008)
The personnel policy is crucial for every company. Its efficiency raises levels of personnel qualifications, good interpersonal relationships, organizational changes and quality of company's products. New competences in HRM are required for the personnel policy to become main source of competitive advantages.
Keywords: zarządzanie zasobami ludzkimi; proces decydowania; rola i umiejętności menedżera; style kierowania; system motywacji pracowników; human resource management; decision-making process; the role and skills of the manager; targeting styles; employee motivation system